Calorific value of Pinus radiata D. Don species to improve pellet production in the District of Acraquia - Tayacaja - Huancavelica (GnosisWisdom, 2024)
This study focused on determining the calorific value of Pinus radiata D. Don wood, a forest species with potential as energy biomass that can be used in the production of pellets. The research was carried out in the chemistry laboratory of the Forestry and Environmental Engineering career, following the methodology of the ASTM-D-2015-66, 1972 standard to determine the experimental calorific value, where the main results were obtained such as: moisture content: 15.38%, Experimental higher calorific value (sample P-01: 4227.4 Kcal/kg and Sample P-02: 4321. 3 Kcal/kg) and the lower calorific value (sample P-01: 3688.4 Kcal/kg and sample P-02: 3782.4 Kcal/kg) based on this it was concluded that the sample P-02 showed the highest calorific value, since the moisture content influences the energy efficiency of the material, these indicates that Pinus radiata D. Don has a significant potential as a source of energy biomass.
Keywords: Calorific power; Pinus radiata D. Don; Biomass